Chest Computed Tomography and Lung Ultrasound Findings in COVID-19 Pneumonia: A Pocket Review for Non-radiologists - Pata, Davide; Valentini, Piero; De Rose, Cristina; De Santis, Rita; Morello, Rosa; Buonsenso, Danilo (Frontiers in Medicine, 2020)
COVID-19 is an infectious disease that rapidly spread worldwide causing a pandemic. The main clinical manifestation is pneumonia. The main exam for diagnosis is represented by RT-PCR but given the limited sensitivity further radiological examinations are necessary. We reviewed the literature to highlight the typical manifestations and advantages of chest computed tomography and lung ultrasound in COVID-19 pneumonia, in order to assist clinical researchers in the management of this disease.